PERBAIKAN METODE DAN MANAJEMEN DALAM UPAYA UPSCALING PRODUKSI DI UKM WARNA CAKE, DESA TEGAL BESAR, JEMBER - Putu Tessa Fadhila; Elly Kurniawati; Resti Pranata Putri (Jurnal Abdi Insani, 2026)
Small and Medium Enterprises (SMEs) are productive businesses carried out by individuals in the form of small home businesses with small-scale production capacity or business entities that meet business criteria. One of the SMEs that produces various wet and dry cakes and bread is Warna Cake in Tegal Besar Permai Housing Complex RT 2 and RW 01 Tegal Besar Village, Kaliwates District, Jember Regency. Warna Cake SMEs face several problems in their efforts to scale up production, namely: 1. Low productivity due to equipment with small production capacity and technology that is not yet adequate to increase production volume and quality, 2. not yet having a NIB (Business Permit Number) and Self Declare Halal and P-IRT which results in limited marketing areas 3. Management of the processing process is still simple so that the quality of products, packaging, labels still do not meet the requirements. 4. Implementation of HACCP has not been carried out properly and comprehensively. The proposing team seeks to help overcome these problems by providing assistance in efforts to increase production capacity through the procurement of equipment with larger capacity and faster performance; assisting in the administrative process at the Jember Regency PLUT for NIB, Halal and P-IRT permits; and providing assistance in Good Manufacturing Practices and introducing the Tangzhong method in order to increase the production capacity of the Warna Cake UKM without reducing the quality of its production.